Analisis Faktor-faktor Produktivitas Padi di Jawa Barat Tahun 2018-2024 - Adiansyah; Jeane Talakua (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of land area variables, climate, fertilizer subsidies, and domestic investment on West Java rice production in 2018-2024. The approach in this study uses a quantitative approach with data in the form of secondary data. The location determination was carried out by the purposive method in the period 2018-2024. The analysis techniques used were in the form of multiple linear regression analysis of panel data with classical assumption test, model specification test, t test, f test, and determination coefficient test. The results of the study show that land area has a significant positive effect on rice production. Meanwhile, climate and domestic investment have a significant negative effect on rice production. And fertilizer subsidies do not have a significant effect on West Java rice production. And the variable that has the most influence on rice production is Land Area.